Teologi Pembebasan Ali Syari’ati (Kajian Humanisme dalam Islam) - Siti Syamsiyatul Ummah (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2020)
Abstract As one of the most prominent Muslim thinkers of modern times, Ali Syari 'ati's role in resisting the repression of Pahlevi's regime is undeniable. He presented himself as a propagandist gusting the spirit of youth in Iran in the 1970's to rise up and resist the authoritarian and oppressive regime of Pahlevi. Ali Syari 'ati had succeeded in building a revolutionary islamic ideology on the foundations of tauhid to elevate degrees and support egalitarianism in humans. In the view of Ali Syari 'ati, tauhid is a oneness between god, human, and the universe. Therefore, any form of social discrimination, injustice, depotism, and persecution must be opposed because it is separate from the rivals of tauhid. It's a library research which deals with liberation theological thinking in the perspective of Ali Syari 'ati in lifting and fighting for emancipation, responsibility and human freedom. The subject of this post is the biography of Ali Syari 'ati, the views of the tauhid world: the tauhid is the free previews of Ali Syari 'ati, the religious humanistic concept Ali Syari'ati, and the tauhid scheme of thought in the religious humanistic concept of Ali Syari'ati. Abstrak Sebagai salah satu pemikir Muslim terkemuka di zaman modern, peran Ali Syari’ati dalam melawan penindasan rezim Pahlevi tidak dapat dimungkiri lagi kebenarannya. Ia tampil sebagai propagandis yang membakar semangat kaum muda di Iran pada 1970-an untuk bangkit dan melawan rezim Syah Pahlevi yang otoriter dan menindas. Ali Syari’ati berhasil membangun ideologi Islam yang revolusioner dengan fondasi tauhid untuk mengangkat derajat dan menyokong egalitarianisme (persamaan) pada manusia. Dalam pandangan Ali Syari’ati, tauhid adalah kesatuan antara Tuhan, manusia, dan alam semesta. Maka, segala bentuk diskriminasi sosial, ketidakadilan, kedzaliman, dan penindasan harus dilawan karena termasuk hal yang syirik (lawan tauhid). Tulisan ini merupakan library research yang membahas tentang pemikiran teologi pembebasan dalam prespektif Ali Syari’ati dalam mengangkat dan memperjuangkan emansipasi, tanggung jawab dan kebebasan manusia. Sub pembahasan dalam tulisan ini adalah biografi Ali Syari’ati, pandangan dunia tauhid: Tauhid yang membebaskan prespektif Ali Syari’ati, konsep religius humanistik Ali Syari’ati, serta skema pemikiran tauhid dalam konsep religius humanistik Ali Syari’ati.